Strategic leadership according to the outstanding banking performance analystical study on private banks - الشمري صادق راشد (Journal of Economics and Administrative Sciences, 2015)
This research aimd to analyze the role of strategic entreprenenial on according to the external performance of a sample of Iraqi private banks, namely, (National Islamic Bank, Iraqi Ahli Bank, Baghdad Bank , Middle East Iraqi Investment Bank) has launched research in fundamental problem stems from the question seeking his response to the characterization of the problem which is improve banking performance through strategic entreprenenial and to achieve the goal of the research was to prepare a questionnaire included a number of questions about the independent research and approved variables accounting for the independent variable strategic entreprenenial and included four dimensions (entreprenenial culture), entreprenenial leadership, mind leading or managed resources strategically. The dependent variable (outstanding performance) the adoption of four metrics are (Financial scale, marketing scale, resources scale, and scale to support senior management. Forms have offered a sample of middle and senior management staff in the four banks to answer it. The study found the research sample to realize the importance of the dimensions of the strategic entreprenenial to achieve outstanding performance and recommends that the adoption of the banks to find a strategic entreprenenial to improve its performance